Climate Risk Profile for Tharaka Nithi County. Kenya County Climate Risk Profile Series - Ministry of Agriculture, Livestock and Fisheries, Kenya (2018)
County Climate Risk Profiles are a key tool to guide climate smart agriculture (CSA) investments and priorities at the county level in Kenya. These documents provide analyses of the underlying causes of vulnerability and on-going and potential climate change adaptation strategies. They also provide a snapshot of the enabling environment for building resilience by providing a synthesis of the policy, institutional and governance context. Complementary materials such as map books and annexes for productivity of major agricultural commodities, climate analysis, adaptation options, and methodological details are also provided.